Reconstructionism in the Philosophy of Education: Transformational Implications For Islamic Religious Education - Bahnur Damau (IAIN KENDARI, 2025)
This study aims to examine the reconstructionism approach in the philosophy of education and its transformational implications for Islamic Religious Education. Through a systematic review of ten relevant scholarly articles, the study finds that reconstructionism views education as a primary instrument for creating progressive social change. In the context of Islamic Religious Education, this approach emphasizes the need to reinterpret Islamic values to remain relevant in addressing modern challenges such as moral crises, spiritual disorientation, and socio-cultural conflicts. The findings indicate that integrating the principles of reconstructionism into Islamic Religious Education has the potential to strengthen students' character through a contextual, reflective, and transformative approach. Core values such as tarbiyah (nurturing), ta‘līm (teaching), and ta’dīb (ethical formation) serve as essential foundations in designing curricula that focus not only on the transmission of knowledge but also on the development of personality and social awareness. Thus, reconstructionism not only enriches the theoretical discourse of Islamic education but also provides new directions in formulating educational policies and practices that are adaptive to contemporary social dynamics. This study recommends a more systematic integration between Islamic educational philosophy and modern critical approaches to produce a more responsive, inclusive, and meaningful religious education system.